2007
DOI: 10.1093/cercor/bhm104
|View full text |Cite
|
Sign up to set email alerts
|

Activating the Medial Temporal Lobe during Oddity Judgment for Faces and Scenes

Abstract: Impairments in visual discrimination beyond long-term declarative memory have been found in amnesic individuals, with hippocampal lesions resulting in deficits in scene discrimination and perirhinal cortex damage affecting object discrimination. To complement these findings, the present functional magnetic resonance imaging study found that in healthy participants oddity judgment for novel trial-unique scenes, compared with face or size oddity, was associated with increased posterior hippocampus and parahippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
143
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 134 publications
(166 citation statements)
references
References 85 publications
19
143
1
Order By: Relevance
“…Unlike several previous studies that have looked at HC responses during scene perception [Barense et al, 2010; Lee et al, 2008; Lee and Rudebeck, 2010b; Mundy et al, 2012; Zeidman et al, 2015], we found stronger group‐level (bilateral) activation in the anterior, rather than posterior, HC (although see Lee et al, 2013). As has been discussed elsewhere, spatial smoothing of EPI data can lead to “blurring” between adjacent anatomical ROIs, such as between PHG and posterior HC [Reber et al, 2002].…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…Unlike several previous studies that have looked at HC responses during scene perception [Barense et al, 2010; Lee et al, 2008; Lee and Rudebeck, 2010b; Mundy et al, 2012; Zeidman et al, 2015], we found stronger group‐level (bilateral) activation in the anterior, rather than posterior, HC (although see Lee et al, 2013). As has been discussed elsewhere, spatial smoothing of EPI data can lead to “blurring” between adjacent anatomical ROIs, such as between PHG and posterior HC [Reber et al, 2002].…”
Section: Discussioncontrasting
confidence: 93%
“…Overall, the results of our group‐level analyses were consistent with previous studies that observed strong scene‐sensitivity in these regions during standard localiser tasks [Bettencourt and Xu, 2013; Epstein, 2008; Epstein and Kanwisher, 1998; Lee et al, 2008; Spiridon et al, 2006]. Our main scene‐selective contrast revealed significant bilateral activity in each tested ROI at the whole brain level, including HC and TOS.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations